Study protocol: a cluster randomised controlled trial of a school based fruit and vegetable intervention - Project Tomato - Conner Mark T; Clarke Graham P; Greenwood Darren C; Ransley Joan K; Kitchen Meaghan S; Jupp Jennifer; Cade Janet E (BMC, 2009)
Abstract Background The School Fruit and Vegetable Scheme (SFVS) is an important public health intervention. The aim of this scheme is to provide a free piece of fruit and/or vegetable every day for children in Reception to Year 2. When children are no longer eligible for the scheme (from Year 3) their overall fruit and vegetable consumption decreases back to baseline levels. This proposed study aims to design a flexible multi-component intervention for schools to support the maintenance of fruit and vegetable consumption for Year 3 children who are no longer eligible for the scheme. Method This study is a cluster randomised controlled trial of Year 2 classes from 54 primary schools across England. The schools will be randomly allocated into two groups to receive either an active intervention called Project Tomato, to support maintenance of fruit intake in Year 3 children, or a less active intervention (control group), consisting of a 5 A DAY booklet. Children's diets will be analysed using the Child And Diet Evaluation Tool (CADET), and height and weight measurements collected, at baseline (Year 2) and 18 month follow-up (Year 4). The primary outcome will be the ability of the intervention (Project Tomato) to maintain consumption of fruit and vegetable portions compared to the control group. Discussion A positive result will identify how fruit and vegetable consumption can be maintained in young children, and will be useful for policies supporting the SFVS. A negative result would be used to inform the research agenda and contribute to redefining future strategies for increasing children's fruit and vegetable consumption. Trial registration Medical Research Council Registry code G0501297